A Pilot Study of 18F-DCFPyL PET/CT or PET/MRI and Ultrasound Fusion Targeted Prostate Biopsy for Intra-Prostatic PET-Positive Lesions - Liu, Yachao; Yu, Hongkai; Liu, Jiajin; Zhang, Xiaojun; Lin, Mu; Schmidt, Holger; Gao, Jiangping; Xu, Baixuan (Frontiers in Oncology, 2021)
Objectives: The purpose of this study was to evaluate the feasibility and diagnostic performance of prostate-specific membrane antigen (PSMA) based 18F-DCFPyL PET/CT-ultrasound (PET/CT-US) or PET/MRI-ultrasound (PET/MRI-US) fusion targeted biopsy for intra-prostatic PET-positive lesions. Methods: From April 2018 to November 2019, we prospectively enrolled 55 candidates to perform PET/CT-US or PET/MRI-US fusion targeted biopsies for solitary PET-positive prostate lesions (2-4 cores/lesion). The positive rates of prostate cancer based on patients and biopsy cores were calculated respectively. With reference to the pathological results of biopsy cores, the MR signal characteristics in the area of the PET-positive lesion were analyzed for the patients who underwent PET/MRI. Results: A total of 178 biopsy cores were taken on the 55 patients. 146 biopsy cores (82.0%, 146/178) from 51 (92.7%, 51/55) patients were positive for prostate cancer; 47 (85.5%, 47/55) were clinically significant prostate cancer. It is noteworthy that 9 patients underwent both 18F-DCFPyL PET/CT and PET/MRI examinations; the 7 patients with prostate cancer showed abnormal MR signal in the area of the PET-positive lesion while the other 2 patients with prostatic hyperplasia and prostatitis showed normal MR signal in the area of the PET-positive lesion. Conclusion: This study indicated that 18F-DCFPyL PET/CT-US or PET/MRI-US fusion targeted prostate biopsies may be valuable for prostate cancer diagnosis and have a high detection rate of clinically significant prostate cancer for PET-positive lesions. PET/MR can rule out some false PET-positive lesions, which may potentially reduce unnecessary prostate biopsies.